Adaptive Collaborative Detection for Opportunistic Vehicle Sensor Networks - Yuanyuan Zeng (International Journal of Distributed Sensor Networks)
Transportation is a huge problem that curbs development of societies and economy in many countries nowadays. Participatory sensing technologies encourage people to be involved in environment monitoring through smart devices. Vehicle sensor networks (VSNs) are a novel solution for road event detection with advantages. In this paper, we consider runtime road event detection using VSNs to satisfy the application-specific requirements through collaboration among vehicles. A group road detection scheme (GRD) by using dynamic clustering in VSNs is presented to improve detection performance with low time complexity and message complexity. The simulations with testbed of 5 remote controllable vehicles show that GRD scheme provides effectiveness under different road scenarios.